An ethnobotanical study of medicinal plants used for skin diseases by the local people in El Bayadh region, Algeria - Toumi, Nadia; Nouri, Zohra; Dellal, Abbes; Bendouma, Oum Enoune; Benarmas, Rachida Benabdallah; Bekri, Fatima Zohra; Dif, Mustapha Mahmoud (Ethnobotany Research and Applications, 2026)
Background: Despite Algeria's rich botanical diversity (approximately 1000 medicinal species among 3139 spermatophytes), ethnobotanical documentation of dermatological uses in rural El Bayadh remains limited. This study documents medicinal plants used by traditional herbalists for treating skin diseases in this region. Methods: Structured questionnaires were administered to 50 herbalists. Data on demographics, plant uses, preparation methods, and administration routes were summarized; the frequency citation index was calculated. Results: Forty-two species from 25 families were recorded for 25 skin diseases. Lamiaceae and Asteraceae were the most represented (11.90% each). Leaves were the most used plant part (25.13%), and oil extraction predominated (38%). Topical administration was most frequent (67%). Reported patient satisfaction was high (89%), often attributed to cost-effectiveness. Several species have not been previously reported for dermatological applications. Conclusions: This first comprehensive documentation for El Bayadh highlights substantial therapeutic knowledge and underscores the urgent need for documentation and conservation given the concentration of this knowledge among elderly practitioners. Background: Despite Algeria's rich botanical diversity (approximately 1000 medicinal species among 3139 spermatophytes), ethnobotanical documentation of dermatological uses in rural El Bayadh remains limited. This study documents medicinal plants used by traditional herbalists for treating skin diseases in this region. Methods: structured questionnaires were administered to 50 herbalists. Data on demographics, plant uses, preparation methods, and administration routes were summarized; the frequency citation index was calculated. Results: Forty-two species from 25 families were recorded for 25 skin diseases. Lamiaceae and Asteraceae were the most represented (11.90% each). Leaves were the most used plant part (25.13%), and oil extraction predominated (38%). Topical administration was most frequent (67%). Reported patient satisfaction was high (89%), often attributed to cost-effectiveness. Several species have not been previously reported for dermatological applications. Conclusions: This first comprehensive documentation for El Bayadh highlights substantial therapeutic knowledge and underscores the urgent need for documentation and conservation given the concentration of this knowledge among elderly practitioners. Keywords: Medicinal plants; Ethnobotany; Dermatological diseases; Traditional medicine; Algeria